Workplace Spirituality and Knowledge Sharing on Employee Engagement: Mediated Role by Achievement Motivation - Mutiara, Athiyyah Nadiya Rianti; Nurhayati, Mafizatun (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
Purpose - This study aims to determine the role of workplace spirituality and knowledge sharing in influencing employee engagement with achievement motivation as a mediating variable.Methodology - Analysis of the model in the study using Partial Least Square (PLS) with SMART PLS Software Ver 4.0 with the sample of this study is an educational foundation located in West Jakarta. The research respondents were permanent teachers, totaling 108 teachers.Findings - This study proves that workplace spirituality and achievement motivation affect employee engagement, knowledge sharing does not affect employee engagement,workplace spirituality and knowledge sharing effect on employee engagement mediated by achievement motivation. Novelty/value - Finding meaning in work can have an impact on feeling attached to the organization and have an impact on increasing achievement motivation in carrying out work. Achievement motivation, if managed, implemented, and developed by an organization, can improve or create a work environment that is spiritual and knowledge sharing between employees will work effectively so that later an organization will have employees with a high level of engagement